Bosnia and Herzegovina : Technical Assistance Report-Government Finance Statistics. (IMF Staff Country Reports; Country Report, 2018)
This Technical Assistance Report discusses the findings and recommendations made by the IMF mission about improving government finance statistics (GFS) for decision making in the Republic of Srpska (RS), Bosnia and Herzegovina. The future delineation of tasks and responsibilities in the Bosnia and Herzegovina GFS compilation process between the Agency for Statistics of Bosnia and Herzegovina (BHAS), Central Bank of Bosnia and Herzegovina (CBBH), Ministry of Finance RS, and Republic of Srpska Institute of Statistics is still open. The current TA can assist the RS authorities to compile aggregated RS level GFS data. Together with comprehensive methodological explanations, comprehensive process tables, and the free flow of GFS relevant data, this should allow CBBH and BHAS to compile consolidated data for Bosnia and Herzegovina.